Experiences with remote laboratories - Andrew Nafalski (2010)
The paper reports on experiences of academics and students involved in using remote engineering laboratories both when students work individually or collaboratively with others on the experiments. Positives and negatives are highlighted and are contrasted with expectations of what the remote laboratories can bring into pedagogical environments. Recommendations and conclusions follow on how to better use the remote laboratories in teaching.